Preoperative 6-minute walk test predicts prolonged hospitalization after transcatheter tricuspid valve replacement. Issue 51 (23rd December 2022) - Chen, Yanjing; Cai, Chengliang; Qiao, Fan; Li, Bailing; Xu, Zhiyun; Lu, Fanglin; An, Zhao
Abstract : The purpose of this study is to determine whether preoperative 6-minute walk test (6MWT) is associated with prolonged postoperative hospitalization in high risk patients with severe tricuspid regurgitation (TR) after transcatheter tricuspid valve replacement (TTVR). Forty-one patients with severe TR who underwent TTVR and discharged between September 2018 and April 2021 were enrolled in this study. Patients were divided into 2 groups according to whether the postoperative hospital stay was >10 days and patients' data were retrospectively collected. 6MWT was performed before operation. Twenty-one patients were in the control group (≤10 days) and 20 patients were in the prolonged postoperative stay (PPS) group (>10 days). 6MWT distance was significantly decreased in PPS group (192.70 ± 62.34 vs 274.57 ± 52.09 m, P < .05). PPS group had more patients with severe liver disease (50.00% vs 19.05%, P < .05), higher systolic pulmonary artery pressure (45.05 ± 9.28 vs 35.57 ± 8.91 mm Hg, P < .05) and longer procedure time (159.85 ± 56.61 vs 124.43 ± 31.67 min, P < .05). Multivariable logistic regression analysis found 6MWT <267 m was an independent risk factor with the odds ratio of 10.95 (1.66–72.39, P < .05) for prolonged postoperative hospitalization in patients who received TTVR. In the present study, we identified that preoperative decreased 6MWT distance was an independent risk factor for prolonged hospitalization in high risk TR patients after TTVR.